2020
DOI: 10.3390/ijerph17103702
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Care in a Remote Aboriginal Community Context: What, When and by Whom?

Abstract: Preconception care (PCC) is acknowledged as a vital preventive health measure aiming to promote health today and for subsequent generations. We aimed to describe the content and context of PCC delivery in a very remote Australian Aboriginal Community Controlled Health Service setting. A retrospective audit was undertaken to identify what PCC was delivered between 2011 and 2018 to 127 Aboriginal women who had at least one pregnancy during this period. Of 177 confirmed pregnancies, 121 had received PCC prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…[33,34] Further supporting evidence for referring to women in the ORCHID cohort as having pregestational prediabetes is the range of lower limits for HbA 1c used internationally to diagnose prediabetes in the nonpregnant population (5.7 to 6.0%, 39 to 42 mmol/mol), [35,36] the~0.5% (~6 mmol/mol) drop in HbA 1c by second trimester, [11] the estimated high levels of prediabetes in young Aboriginal people from Northern Australia (12-28%), [5] and less than optimal preconception screening coverage. [6] Differentiation of women with 'pregestational prediabetes' (16.3% of Aboriginal women in our cohort with HbA 1c 5.6%, 38 mmol/mol) from those who develop GDM in the second half of pregnancy (12.4% of Aboriginal women in our cohort) may be clinically relevant. A review of several small studies in women referred for self-monitoring of blood glucose based on elevated early HbA 1c showed pharmaceutical intervention is often required prior to 24-weeks gestation in women with HbA 1c 5.7-5.9% (39-41 mmol/mol).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…[33,34] Further supporting evidence for referring to women in the ORCHID cohort as having pregestational prediabetes is the range of lower limits for HbA 1c used internationally to diagnose prediabetes in the nonpregnant population (5.7 to 6.0%, 39 to 42 mmol/mol), [35,36] the~0.5% (~6 mmol/mol) drop in HbA 1c by second trimester, [11] the estimated high levels of prediabetes in young Aboriginal people from Northern Australia (12-28%), [5] and less than optimal preconception screening coverage. [6] Differentiation of women with 'pregestational prediabetes' (16.3% of Aboriginal women in our cohort with HbA 1c 5.6%, 38 mmol/mol) from those who develop GDM in the second half of pregnancy (12.4% of Aboriginal women in our cohort) may be clinically relevant. A review of several small studies in women referred for self-monitoring of blood glucose based on elevated early HbA 1c showed pharmaceutical intervention is often required prior to 24-weeks gestation in women with HbA 1c 5.7-5.9% (39-41 mmol/mol).…”
Section: Discussionmentioning
confidence: 81%
“…[3,4] In the broader population the prevalence of prediabetes going into pregnancy is unclear due to less-than-optimal preconception screening, especially in high-risk Indigenous women. [5][6][7] To improve birth outcomes recent (2020) Australasian Diabetes in Pregnancy Society (ADIPS) guidelines recommend women with prediabetes (fasting plasma glucose (FPG) 6.1-6.9 mmol/L; or 2-h plasma glucose (PG) 7.8-11.0 mmol/L; or HbA 1c 6.0-6.4%, 42-46 mmol/mol) be managed as having GDM from conception. [8] The first antenatal visit presents as an opportunity to detect prediabetes, however nonpregnancy thresholds for diagnosis may be inappropriate due to changes in FPG and glycated hemoglobin (HbA 1c ) throughout pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported on women’s access to preconception health information and/or care ( Table 4 ) [ 44 , 76 ]. Other studies focused on specific topics or health conditions such as folic acid information [ 96 ] and women with heart disease receiving preconception counselling [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen papers examined NCDs in the context of healthcare disparities. Fourteen of these papers were from the US [ 10 , 11 , 16 , 21 , 32 , 40 , 55 , 56 , 97 , 105 , 107 , 119 , 140 , 150 ], two papers from Australia [ 54 , 57 ] one paper each from Brazil [ 19 ] and India [ 88 ]. One of the papers was published by the Centers for Disease Control and Prevention (CDC) from the US in collaboration with the Ministry of Health in Brazil and Pan Americana Health Organization (PAHO) and looked at the association between factors like race, education and insurance status in Brazilian reproductive age women [ 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the US-based papers focused on a wide range of topics including disparities in insurance coverage, mental health service utilization, chronic disease risk factors, hospitalization in pregnant women with NCDs, medication discontinuation and sexual orientation and health care access. The two papers from Australia focused on Aboriginal women with one paper looking at pre-conception care and the other paper reporting on stakeholder input on health service planning for reproductive age Aboriginal women with NCD risk factors [ 54 , 57 ]. The paper from Brazil, an upper middle income country, examined inequities in NCD indicators in reproductive age women who were beneficiaries of a government-based social welfare program [ 19 ].…”
Section: Resultsmentioning
confidence: 99%